Circuit training intervention for cognitive function, gut microbiota, and aging control: study protocol for a longitudinal, open-label randomized controlled trial - Keishi Soga; Michio Takahashi; Akari Uno; Takamitsu Sinada; Kentaro Oba; Keisei Kawashima; Yasuko Tatewaki; Taizen Nakase; Yasuyuki Taki (Trials)
Abstract Background Long-term exercise is increasingly considered an effective strategy to counteract cognitive decline associated with aging. Previous studies have indicated that circuit training exercises integrating aerobic and resistance modalities positively affect cognitive function. Furthermore, a growing body of evidence suggests that long-term exercise alters the gut microbiota, leading to an optimal environment for cognitive enhancement. Recent empirical evidence suggests that exercise plays a significant role in modulating aging-control factors at the protein level. Although the interaction between exercise and cognitive function is multifaceted, most studies have only examined a direct pathway from exercise to cognitive function. Therefore, this study aims to elucidate the effects of long-term circuit training on cognitive function through a comprehensive analysis of factors such as gut microbiota and proteins related to aging control. Methods A total of fifty-one participants will be randomly assigned to either the circuit training or waitlist control group. The intervention group will participate in a circuit training program developed by Curves Japan Co., Ltd. two to three times weekly for 16 weeks. The control group will continue their usual daily routines without participating in any new active lifestyle program. The participants will undergo cognitive assessments at baseline and after the intervention. Fecal and blood samples for protein analysis will be collected before and after the intervention. The effect of exercise on cognition will be analyzed by comparing the measured outcomes before and after the intervention. The associations among these outcomes will be assessed using a linear mixed model and structural equation modeling approaches. Discussion This study aims to provide the first insights into the comprehensive effects of exercise on cognitive function from the perspectives of gut microbiota and aging control. The findings are expected to contribute to improving brain health and combating age-related cognitive decline. Furthermore, the findings may help establish new guidelines for future studies on the relationship between exercise and cognitive function.